1981
DOI: 10.1002/1097-0142(19811201)48:11<2485::aid-cncr2820481123>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study of thymomas with special reference to their clinical stages

Abstract: Follow-up data were obtained for 96 cases of thymoma. The one-year survival rate was 84.3%, the three-year 77.1%, the five-year 74.1%, and the ten-year 57.1%. The five-year survival rate of total resection group was 88.9%; that of non-radically treated group was 44.4%. Clinical stages were defined: Stage I--macroscopically encapsulated and microscopically no capsular invasion; Stage II--1. macroscopic invasion into surrounding fatty tissue of mediastinal pleura, or 2. microscopic invasion into capsule; Stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
844
1
46

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,543 publications
(905 citation statements)
references
References 16 publications
14
844
1
46
Order By: Relevance
“…Of the 305 MG patients, there were 110 cases with positive anti-AchR and 195 cases with negative anti-AchR. Besides, according to Osserman's classification, 13 there were 126 ocular MG patients and 179 generalized MG patients.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Of the 305 MG patients, there were 110 cases with positive anti-AchR and 195 cases with negative anti-AchR. Besides, according to Osserman's classification, 13 there were 126 ocular MG patients and 179 generalized MG patients.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Myasthenia gravis was related to disease in 130 patients. The classification system of Masaoka et al 3 was adopted as the staging system, and tumors classified as Stage II, III or IV disease were considered invasive. Involvement of the great vessels (the brachiocephalic veins, superior vena cava, and aorta) was confirmed by critical review of the surgical records.…”
Section: Patientsmentioning
confidence: 99%
“…Survival curves according to the staging system of Masaoka et al 3 are shown in Figure 1 classification system are shown in Figure 2. The 20-year survival rates were 100% for patients with type A tumors, 87% for patients with type AB tumors, 91% for patients with type B1 tumors, 59% for patients with type B2 tumors, and 36% for patients with type B3…”
Section: Survival According To the Putative Prognostic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,13,14 Clinical follow-up was obtained in each case; duration of survival and outcome were recorded. The cases were staged according to the criteria proposed by Masaoka et al: 15 Stage 1: macroscopically completely encapsulated and microscopically no capsular invasion; Stage 2a: macroscopic invasion into surrounding fatty tissue mediastinal pleura or both; Stage 2b: microscopic invasion into capsule; Stage 3: macroscopic invasion into a neighboring organ (pericardium, great vessel, lung, etc); Stage 4a: pleural and/ or pericardial dissemination; Stage 4b: lymphogenous and/or hematogenous metastasis. A lung primary tumor was excluded in all patients.…”
Section: Methodsmentioning
confidence: 99%